Microstructural, cytotoxicity and antibacterial properties of bio-degradable Zn-2Cu-Ti alloy. (2021) - Arunkumar, G.; Rameshbabu, A.M.; Parameswaran, P.; Kumar, T. Raj; Radha Krishnan, K.
Abstract: Scientist uses zinc alloy in the field of bio-medical engineering due its excellent combinations of degradation rates, hemo-compatibility, anti-bacterial activities, etc. The pure zinc metal anyhow suffers lack in strength, mechanical properties due to its hexagonal closed pack structure, which makes it brittle during mechanical working and other operations. In this research we have fabricated a new alloy combination of zinc which includes the addition of copper (Cu) and titanium (Ti) in very smaller proportion through powder metallurgy route. Zn-2Cu-2Ti was the fabricated alloy combination, in which hardness and microstructural properties were studied. The phases observed were CuZn5, with intermetallic phase of TiZn16 . Based on the results, the newly made alloy showed good improvement in the bio-compatibility and anti-bacterial activity. Hence we can suggest the material for bone implants and bio-degradable stunts.